Attitudes towards Zika screening and vaccination acceptability among pregnant women in Malaysia - Wong, Li Ping; Alias, Haridah; Hassan, Jamiyah; AbuBakar, Sazaly (Elsevier, 2017)
The aim of this study was to examine the willingness of pregnant women to have prenatal screening for the Zika virus (ZIKV). Secondly, the study also assessed the acceptability of a hypothetical Zika vaccination and its association with the health belief model (HBM) constructs. A cross-sectional study was conducted from 4th October to 11th November 2016, among pregnant women who attended antenatal care at the University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia. The majority (81.8%) was willing to be tested for ZIKV and 78% felt that their spouse would be willing to be tested for ZIKV. A total of 94% expressed a willingness to receive a Zika vaccination if available. The participants expressed high perceived benefits of a ZIKV vaccination. Although many have a high perception of the severity of ZIKV, the proportion with a strong perception of their susceptibility to ZIKV was low. In the multivariate analysis of all the HBM constructs, cue-to-action, namely physician recommendation (odds ratio [OR] = 2.288; 95% confidence interval [CI] 1.093–4.793) and recommendation from friends or relatives (OR = 4.030; 95% CI 1.694–9.587), were significantly associated with a willingness to be vaccinated against ZIKV. The favourable response to a Zika vaccination implies that more research attention has to be given to develop a vaccine against ZIKV. Should the vaccine be available in the future, publicity and healthcare providers would play a vital role in ensuring vaccine uptake among pregnant women.